2022
DOI: 10.3390/cells11244129
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Mesenchymal Stem Cells in the Treatment of Epilepsy and Their Interaction with Antiseizure Medications

Abstract: Epilepsy is a life-threatening neurological disease that affects approximately 70 million people worldwide. Although the vast majority of patients may be successfully managed with currently used antiseizure medication (ASM), the search for alternative therapies is still necessary due to pharmacoresistance in about 30% of patients with epilepsy. Here, we review the effects of ASMs on stem cell treatment when they could be, as expected, co-administered. Indeed, it has been reported that ASMs produce significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 153 publications
0
3
0
Order By: Relevance
“…Recent clinical trials of anti-A β antibodies reported that deterioration of clinical symptoms was slowed, but symptoms themselves were not improved [ 24 , 25 ], while it was not yet clear whether anti-tau treatments also can improve clinical symptoms [ 26 , 27 ]. Notably, in other neurological diseases, such as stroke, traumatic injury, and epilepsy, MSCs have been shown to perform therapeutic effects through attenuating neuroinflammation as well as inducing angiogenesis [ 28 30 ]. Neuroinflammation as well as vascular dysfunction or blood-brain barrier (BBB) breakdown is thought to be involved in the pathogenesis of AD [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials of anti-A β antibodies reported that deterioration of clinical symptoms was slowed, but symptoms themselves were not improved [ 24 , 25 ], while it was not yet clear whether anti-tau treatments also can improve clinical symptoms [ 26 , 27 ]. Notably, in other neurological diseases, such as stroke, traumatic injury, and epilepsy, MSCs have been shown to perform therapeutic effects through attenuating neuroinflammation as well as inducing angiogenesis [ 28 30 ]. Neuroinflammation as well as vascular dysfunction or blood-brain barrier (BBB) breakdown is thought to be involved in the pathogenesis of AD [ 31 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other drugs: during the last few years several other antineoplastic drugs have been studied as potential carriers by MSC; in a preclinical study by Kosaka et coll., concurrent administration of 5-fluorocytosine and MSC bound to cytosine deaminase led to significant survival improvement in rats with gliomas [ 23 ]; similarly, Ryu et coll. disclosed that thymidine kinase loaded MSC by herpes simplex I virus improved overall survival in a similar population of mice [ 24 ]. Xiao et al reported that silica nanorattle-doxorubicin compounds can be fixed to MSC in nanoparticulate patches which are able to migrate towards U251 tumor cells both in vivo and in vitro [ 25 ].…”
Section: Drugs That Can Be Delivered By Mscmentioning
confidence: 99%
“…In the light of this recently acquired knowledge, regenerative medicine of the NS is emerging as a new challenge for the scientific world. Current studies showed that stem-cell-based therapy can offer beneficial effects for several NSDs, such as stroke [365][366][367], epilepsy [368,369], PD [370][371][372], and other chronic neurodegenerative disorders. Organoids containing neural stem cells and neural progenitor cells are proposed as rich sources of autologous cells and tissue transplantation.…”
Section: Brainmentioning
confidence: 99%